Video-making Projects for TPACK Development of Pre-service EFL Teachers - Fadhila Yonata; Heris Sandra; Serly Serly; Nefya Ortapia; Lasri Novita Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study examines the impact of the video-making project assigned for pre-service teachers in English education department to enhance their competences of TPACK. Anchored in a qualitative approach, semi-structured interview with six student teachers in second semester was conducted to gain their voices on whether producing video as part of tasks in two English subjects facilitated them on learning new insight related to technology, pedagogy and content of some materials. Findings reveal video-making projects promoted self-eagerness to improve self-competence and collaboration with peers and lecturers. Consequently, making a video as tasks showed a potential for developing pre-service teachers’ TPACK. Participants’ voices indicated there were some challenges in video producing process. The study also suggests that there is ample room for improvement especially in preparing student teachers with prior knowledge of using technology.